Educators of Urban ProJovem: Who are these young actors of youth and adult education? - Pinheiro, Diógenes; Esteve, Luiz Carlos Gil; Farah Neto, Miguel (Education Policy Analysis Archives, 2014)
The National Youth Inclusion Program -Urban- established in 2005 as an emergency and experimental action, among those implemented by the federal government for the setting up of a National Youth Policy, is the best-known initiative aimed at young Brazilians by the population. In 2012, after seven years under the management of the National Youth Secretariat, it had its coordination transferred to the Ministry of Education, being incorporated by the area of youth and adult education. In this context, it is important to know the educators who, until then, acted on it: who are they? What differences are there between them and the other teachers? What are close and far in relation to other experiences? Seeking to answer these questions, this study is based on data collected in 2009 in 11 states, with a sample of 419 educators. Among its findings, it highlights the fact that almost all of them (97.8 %) have higher education. In addition, 64.9 % attended some post graduation. Whereas 74.9% teach for less than 10 years, it appears that these teachers have higher education than most professionals traditionally linked to this educational modality. To this end, the conditions of implementation of the Program, on the selection and preparation of teachers, may represent a significant achievement. Learning more about these actors is the way to understand important aspects of the work developed by the government when setting ProJovem and may provide insights to the qualification and / or redefinition of the Program, now a major public EJA policy in Brazil.